Bis(amino)phosphines Derived From N-phenylpiperazine and N-ethylpiperazine: Synthesis, Oxidation Reactions, and Molybdenum Complexes - Sarioz, Ozlem; Oznergiz, Sena; Kandemirli, Fatma (Informa UK Limited, 2012)
Functionalized bis(amino)phosphines that are the type PhP(NR2)2 (1,2) have been synthesized by treating PhPCl2 with N-phenylpiperazine or N-ethylpiperazine. Ligands react with aqueous hydrogen peroxide, elemental sulfur, or selenium to give the corresponding chalcogenides (3–8) in good yield. The molybdenum complexes of the bis(amino)phosphines (9,10) have been obtained. All of the compounds obtained in good yields and they were characterized by IR, NMR, microanalysis, and also quantum chemical calculations such as HOMO-LUMO energies, Mulliken charges, and dipole moment for compounds 1–8 and complex 9 were carried out by using B3LYP/6-31G(d,p), a version of the DFT method with standard Gaussian 09 software package program.
Keywords: synthesis; oxidation; aminophosphines; quantum chemical calculations